PERAN DANA DARURAT DAN PERENCANAAN PENSIUN DALAM KESEJAHTERAAN KEUANGAN MILENIAL INDONESIA - Muhammad Fazli; Sheltya Sheltya; Agnes Agnes (Komunitas Manajemen Kompetitif, 2026)
Indonesian millennials face distinctive financial pressures, ranging from income uncertainty and rising living costs to the burden of being a sandwich generation. Amid these conditions, emergency fund ownership and pension program participation remain very low, potentially eroding both short-term and long-term financial well-being. This study aims to analyze the role of emergency funds and retirement planning on the financial well-being of Indonesian millennials. The method is a literature study (library research) with a content analysis approach to secondary data, including the OJK–BPS National Survey on Financial Literacy and Inclusion (SNLIK), financial institution reports, and relevant academic literature. The analysis is grounded in three theoretical frameworks: the concept of financial well-being (CFPB, 2017), the life-cycle hypothesis (Modigliani & Brumberg, 1954), and the theory of financial literacy (Lusardi & Mitchell, 2014). The findings show that emergency funds act as a liquidity buffer maintaining short-term stability and shock-absorbing capacity, while retirement planning ensures long-term financial sustainability through accumulation and compound interest. Together, both complementarily build the sense of financial security and freedom of choice at the core of financial well-being. The low ownership of emergency funds (±16 percent) and pension participation (±14 percent) among millennials are the main obstacles. The study recommends strengthening financial literacy, automating fund allocation, and policy and employer support